2021
DOI: 10.3390/v13091879
|View full text |Cite
|
Sign up to set email alerts
|

The Immunology of SARS-CoV-2 Infection and Vaccines in Solid Organ Transplant Recipients

Abstract: Since its outbreak in December 2019, the coronavirus disease 2019 (COVID-19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), led to an enormous rise in scientific response with an excess of COVID-19-related studies on the pathogenesis and potential therapeutic approaches. Solid organ transplant (SOT) recipients are a heterogeneous population with long-lasting immunosuppression as a joining element. Immunocompromised patients are a vulnerable population with a high risk of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 165 publications
(189 reference statements)
3
25
0
Order By: Relevance
“…Although not statistically significant, the lower prevalence of SARS-CoV-2 antibodies in transplanted compared to non-transplanted pwCF is in line with the figures reported in non-CF transplanted patients [8] . This finding may be related to several factors, including a more cautious attitude towards the risk of infection, the recommendations for self-isolation provided by the CF centres, but also to a possible low seroconversion rate [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although not statistically significant, the lower prevalence of SARS-CoV-2 antibodies in transplanted compared to non-transplanted pwCF is in line with the figures reported in non-CF transplanted patients [8] . This finding may be related to several factors, including a more cautious attitude towards the risk of infection, the recommendations for self-isolation provided by the CF centres, but also to a possible low seroconversion rate [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on vaccination-induced anti-SARS-CoV-2 immunity showed an impaired response among kidney transplant recipients, whereas HD patients reached almost healthy-control levels [ 34 , 35 , 36 , 37 ]. A recent study showed that after two doses of mRNA vaccination, >95% of dialysis patients presented anti-S IgG antibodies, while only 63.3% of KTR seroconverted with substantially lower antibody levels.…”
Section: Discussionmentioning
confidence: 99%
“…Solid organ transplant (SOT) recipients receive immunosuppressive therapy to prevent allograft rejection, leaving them at higher risk of infections and infection-related morbidity and mortality (1). This may also be true for coronavirus disease 2019 (COVID-19) (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…However, SOT recipients were not included in these trials (7)(8)(9). Reports on the short-term response to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) mRNA vaccines in SOT recipients indicate that the humoral response after two doses of vaccine (5,6,(10)(11)(12)(13)(14)(15)(16)(17)(18) is inferior to what was initially reported in immunocompetent populations (7,8).…”
Section: Introductionmentioning
confidence: 99%